Pengaruh Penerapan Model UTAUT Terhadap Niat Menggunakan Aplikasi - Putra, Muhammad Rizqi Mubarrok Dwi; Anggraeni, Rila (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This study aims to examine the influence of applying the Unified Theory of Acceptance and Use of Technology (UTAUT) model on the intention to use the Ruangguru learning application. The population in this study consists of primary school parents in Malang City who have never used the Ruangguru learning application before. The sampling technique employed was a non-probability sampling method called purposive sampling with a sample size of 108 respondents. The quantitative data was collected through a questionnaire. The data analysis technique used was multiple linear regression analysis with the assistance of SPSS software version 19.0. The findings of this study indicate that performance expectancy (X1), effort expectancy (X2), social influence (X3), and facilitating condition (X4) have contributions to the intention (Y) to use the Ruangguru application. The implications of this study highlight that there are many factors that influence users to use Ruangguru learning application including pleasant experiences, ease of use, social influence, and availabilities of facilities and supports. Abstrak Penelitian ini bertujuan untuk menguji pengaruh penerapan model UTAUT (Unified Theory Acceptance and Use of Technology) terhadap niat untuk menggunakan aplikasi pembelajaran Ruangguru. Populasi pada penelitian ini adalah wali siswa SD di Kota Malang yang belum pernah menggunakan aplikasi pembelajaran Ruangguru. Teknik pengambilan sampel yang digunakan adalah teknik non-probability sampling metode purposive sampling dengan sampel sejumlah 108 responden. Data dalam penelitian ini diperoleh melalui kuesioner. Teknik analisis data yang digunakan adalah analisis regresi linier berganda dengan bantuan software SPSS versi 19.0. Hasil penelitian menunjukkan bahwa performance expectancy (X1), effort expectancy (X2), social influence (X3), dan facilitating condition (X4) memiliki kontribusi terhadap niat (Y) untuk menggunakan aplikasi Ruangguru. Implikasi dari penelitian ini menyebutkan beberapa factor yang mempengaruhi pengguna menggunakan aplikasi pembelajaran Ruangguru termasuk pengalaman yang menyenangkan, kemudahan penggunaan, pengaruh social, dan ketersediaan fasilitas serta dukungan.